2005
DOI: 10.1016/j.ajo.2004.09.039
|View full text |Cite
|
Sign up to set email alerts
|

Objective analysis of retinal damage in HIV-positive patients in the HAART era using OCT

Abstract: PURPOSE-To assess retinal nerve fiber layer (RNFL) thickness in patients with human immunodeficiency virus (HIV) disease without cytomegalovirus retinitis (CMV). DESIGN-A case-control study.METHODS-The study included 113 eyes of 65 patients in one center. Thickness of RNFL along a 3.4-mm-diameter circle centered on the optic nerve head was evaluated using third-generation optical coherence tomography. Patients in group A (39 eyes of 22 patients) were human immunodeficiency virus-negative control subjects. Grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
63
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 31 publications
1
63
0
Order By: Relevance
“…Similar to our results, observations between those two retinal areas that reached statistical significance, however, were described in works by Varma 19 and later reports by Schuman 13 and are also supported by histologic data. 20 It is interesting that, like Kozak and associates, 17 our results show that the nasal retinal area has the less significant thinning. Interestingly, the areas of RNFL thinning in our HIV-positive patients correspond with the distribution of cotton-wool spots in patients with AIDS as described by Mansour and associates.…”
Section: Discussionmentioning
confidence: 70%
“…Similar to our results, observations between those two retinal areas that reached statistical significance, however, were described in works by Varma 19 and later reports by Schuman 13 and are also supported by histologic data. 20 It is interesting that, like Kozak and associates, 17 our results show that the nasal retinal area has the less significant thinning. Interestingly, the areas of RNFL thinning in our HIV-positive patients correspond with the distribution of cotton-wool spots in patients with AIDS as described by Mansour and associates.…”
Section: Discussionmentioning
confidence: 70%
“…6 It is hypothesized that damage to the inner retina caused by retinovascular abnormalities, including retinal cotton wool spots, leads to permanent impairment of the ganglion cell layer and RNFL with consequent visual function deterioration. [1][2][3][4][5]7,8 A strong spatial correlation has been observed between peripapillary RNFL damage measured by OCT and VF sensitivity in glaucoma. [9][10][11][12] This relationship has also been observed in other optic neuropathies, including compressive 13,14 and ischemic optic neuropathies.…”
mentioning
confidence: 92%
“…RETINA 32:152-159, 2012 P atients infected by the human immunodeficiency virus (HIV), even those without a history of infectious retinitis, experience an optic nerve axonal loss that has been documented through retinal nerve fiber layer (RNFL) evaluation using laser scanning ophthalmoscopy (Heidelberg Retina Tomograph, Heidelberg Engineering, Heidelberg, Germany), 1,2 scanning laser polarimetry (GDx, Carl Zeiss Meditec, Dublin, CA), 2,3 and optical coherence tomography (OCT). 4 Visual field (VF) function abnormalities have also been observed in these patients; in a large cohort study of HIV-infected patients without infectious retinitis, 39% of the eyes displayed abnormal results on standard automated perimetry, 5 and a pattern of early VF loss has been shown to involve the superior and inferior regions. 6 It is hypothesized that damage to the inner retina caused by retinovascular abnormalities, including retinal cotton wool spots, leads to permanent impairment of the ganglion cell layer and RNFL with consequent visual function deterioration.…”
mentioning
confidence: 97%
“…However, a more common cause of optic atrophy in patients without significant retinopathy is AIDS-associated primary optic neuropathy. Generally up to 50% of axons within the optic nerve can be lost before the discs appear atrophic 38 but even asymptomatic HIV patients have axonal loss out of proportion to their degree of demyelination. 72 HIV-related optic neuropathy may occur more commonly than HIV retinopathy, as one autopsy study found HIV in 80% of optic nerves but only 20% of retinas.…”
Section: Neuro-ophthalmologic Findingsmentioning
confidence: 99%